ChemInform Abstract: Ceramics in Environmental Catalysis: Applications and Possibilities. Issue 10 (7th March 2013) - Labhsetwar, Nitin; Doggali, P.; Rayalu, S.; Yadav, R.; Mistuhashi, T.; Haneda, H.
Abstract Review: 57 refs.